Eating Fish: Maximizing the Benefits and Minimizing the Risk - Ken Rosenman; David Solomon; Kari Hortos; Rebecca McAdam (Association of American Medical Colleges, 2012)
Abstract Eating fish is generally accepted as an important part of a healthy diet. The American Heart Association diet and lifestyle recommendations suggest consuming oily fish at least twice a week. Although consuming fish has important health benefits, it also poses some potential risks. Certain fish contain significant levels of chemicals that can potentially be harmful, particularly for children and women of childbearing age. Understanding the risks and benefits of eating fish and being able to effectively counsel patients on how to maximize the benefits and minimize the risks are important skills for physicians, especially those who practice in areas where fish consumption is high and/or sport fishing is a common activity. This resource provides a comprehensive set of educational materials on a narrow but important topic particularly for those trainees who will be practicing in the Great Lakes basin. The materials include lecture slides for a 60-minute talk appropriate for audiences from medical students through practicing physicians. A short multiple-choice quiz assesses the key points of the lecture slides and is also suitable for use as a self-assessment instrument. Also included are materials for three simulated patient cases designed to allow trainees to practice assessing risk and counseling patients on safe fish-eating practices. The presentation has been given to third-year medical students, residents, and practicing physicians and has received excellent reviews.